(untitled) - Sapadin, Linda (Hoboken, N.J., 2004)
This engaging and illuminating self-help book will help readers understand the five styles of fear, showing how these styles affect how we think, speak, act, and live. A fearful, anxious lifestyle can restrict our activities, constrict our thinking, limit our choices, and minimize our enjoyment without making life any safer. Dr. Linda Sapadin offers a prescriptive eight-step program for change, helping readers get past their fears and feel more in control of their lives. She includes helpful, real-life stories of her work with clients.
Keywords: Fear,Self-actualization (Psychology)